2020
DOI: 10.1136/bmjopen-2020-038572
|View full text |Cite
|
Sign up to set email alerts
|

Built form and depression among the Chinese rural elderly: a cross-sectional study

Abstract: ObjectivesFew data on the association between housing structure and depression among rural elders in China are available. We examined the impact of built forms on depression.DesignThis is a cross-sectional study.SettingA representative sample of rural residents aged 60 years or older in China.ParticipantsA total of 5090 older adults in 2019 in rural Suzhou, China.Outcome measuresAssociations of built form with odds of probable and possible depression.ResultsThere was significant difference among elders living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In China, the prevalence of depression shows marked regional differences, which in urban and rural areas are 16% and 30%, respectively (Yang et al, 2019). This may be related to the poor economic development and medical and health services in rural areas (Qiu et al, 2020). This effect is more pronounced among CLD participants who are living in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the prevalence of depression shows marked regional differences, which in urban and rural areas are 16% and 30%, respectively (Yang et al, 2019). This may be related to the poor economic development and medical and health services in rural areas (Qiu et al, 2020). This effect is more pronounced among CLD participants who are living in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…At a household level, a UK study found self-reported overcrowding to be associated with poorer mental well-being . Cross-sectional studies in Asia have reported similar findings . At a mesoscale of residential building, block density has also been used as a marker of crowding.…”
Section: Introductionmentioning
confidence: 96%
“…8 Cross-sectional studies in Asia have reported similar findings. 9,10 At a mesoscale of residential building, block density has also been used as a marker of crowding. An ecological study in Chicago reported the number of units per block to be the second most important housing feature (following the number of persons per room) associated with social aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health deterioration is mainly manifested in losing confidence in life and believing that life is meaningless (9,10). For a long time, the mental health of elderly adults in rural areas has been of interest to scholars, mainly focusing on the influencing factors like family population mobility (11)(12)(13), medical and social endowment insurance (14)(15)(16), widowhood, and disability (17)(18)(19), and so on. It is not difficult to find that most of the present studies are related to the perspective of "negative aging" to explore how to improve the mental health of rural elderly adults.…”
Section: Introductionmentioning
confidence: 99%